2016
DOI: 10.7863/ultra.15.10042
|View full text |Cite
|
Sign up to set email alerts
|

Multiterritory Atherosclerosis and Carotid Intima‐Media Thickness as Cardiovascular Risk Predictors After Percutaneous Angioplasty of Symptomatic Subclavian Artery Stenosis

Abstract: In patients with symptomatic subclavian artery stenosis, baseline carotid intima-media thickness and ICA stenosis of 50% or greater are associated with multiterritory atherosclerosis, whereas intima-media thickness progression is associated with the risk of cardiovascular events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Notably, IMT is associated not only with CAD but also with pan-vascular atherosclerosis. Wrotniak et al in their recent study observed that IMT > 1.3 mm was an independent predictor of multi-territorial atherosclerosis [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, IMT is associated not only with CAD but also with pan-vascular atherosclerosis. Wrotniak et al in their recent study observed that IMT > 1.3 mm was an independent predictor of multi-territorial atherosclerosis [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…CIMT assessment, with or without carotid plaque inclusion, was considered a surrogate measure of atherosclerosis to provide information on the CV outcome in asymptomatic patients with CV risk factors and patients with known atherosclerotic disease, or to measure the effect of medical therapy [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Carotid plaque presence, its number and size, volume, surface, echogenicity, or vascularization are all possible measures of MACCE [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Additionally, in secondary prevention for high-risk patients who already suffered from MI or stroke, the carotid atherosclerosis burden may have a role in the prediction of recurrent MACCE [ 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…A potential indicator of cardiovascular risk might be carotid intima-media thickness (CIMT). Although baseline CIMT is independently associated with the extent of atherosclerosis and ischemic cardiovascular events [13, 14], little is known about whether CIMT change may address atherosclerosis growth in other than carotid artery territory in individual patients, and as such whether CIMT change may be related to risk of major adverse cerebral and coronary events (MACCE), recurrent MI or recurrent angina.…”
Section: Introductionmentioning
confidence: 99%